2003
DOI: 10.1136/heart.89.8.913
|View full text |Cite
|
Sign up to set email alerts
|

Review of diagnosis, treatment, and outcome of fetal atrial flutter compared with supraventricular tachycardia

Abstract: Objective: To review the diagnosis, treatment, and outcome of fetal atrial flutter compared with supraventricular tachycardia. Design: Retrospective review of published reports: 11 papers about fetal tachyarrhythmia published between 1991 and 2002 were selected for review. Main outcome measures: All selected studies were analysed for the type of arrhythmia, degree of atrioventricular block in atrial flutter, occurrence of hydrops fetalis, gestational age at diagnosis, first and second line drug treatment, asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
132
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(147 citation statements)
references
References 26 publications
7
132
0
8
Order By: Relevance
“…Sotalol use has typically been indicated as a second-line agent in the treatment of long VA tachycardias 5,7 and AF 6,11,12 in utero. We documented the mechanism of tachycardia in most fetuses, and although we found it of interest to have a better sense of the mechanism of therapy, our treatment strategy and the clinical outcomes with sotalol therapy were not influenced by the knowledge of the mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Sotalol use has typically been indicated as a second-line agent in the treatment of long VA tachycardias 5,7 and AF 6,11,12 in utero. We documented the mechanism of tachycardia in most fetuses, and although we found it of interest to have a better sense of the mechanism of therapy, our treatment strategy and the clinical outcomes with sotalol therapy were not influenced by the knowledge of the mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, summarized by Krapp et al, 18 reported comparable prenatal success rates in terminating AF and SVT with digoxin, but response times were usually not evaluated. We found that, although prenatal rhythm control was eventually obtained in a significant proportion of chronically treated fetuses, the response of AF to transplacental therapy differed substantially from other forms of SVT.…”
Section: Arrhythmia Typementioning
confidence: 99%
“…This may result in fetal hemodynamic compromise and development of nonimmune hydrops fetalis that can lead to fetal demise. Hydrops fetalis occurs in about half of these cases, with fetal demise occurring in 9% of untreated FT cases 2, 5, 6…”
mentioning
confidence: 99%